Digital Marketing Communication and Tourism Sales at Ibarbo Park Yogyakarta - Eka Miftahul Jannah; Dyaloka Puspita Ningrum (Jobmark: Journal of Branding and Marketing Communication, 2025)
In the digital era, tourism destinations increasingly rely on digital marketing communication to enhance visibility and drive visitor conversion. This study examines the role of digital marketing communication in increasing tourism sales at Ibarbo Park in Sleman, Yogyakarta, using the AISAS model, which comprises Attention, Interest, Search, Action, and Share. The research aims to analyze how each stage of the AISAS framework is implemented to influence consumer behavior and support sales growth. A qualitative interpretive case study approach was employed. Data were collected through in-depth interviews with management, staff, visitors, and the general public, complemented by observation and analysis of digital content on Instagram and TikTok. The data were analyzed thematically to identify patterns of communication strategies across the AISAS stages. The findings reveal that digital marketing communication plays a significant role across all stages of AISAS. Attention is effectively generated through visually engaging content and influencer collaborations. Interest is developed by highlighting the destination's educational and recreational value for families. Search behavior is supported by responsive social media interaction despite the absence of an official website. Action is facilitated through accessible ticket purchasing and a variety of promotional offers, while Share is driven by user-generated content that amplifies organic promotion. Theoretically, this study contributes to the development of digital marketing communication in tourism by contextualizing the AISAS model within local destination marketing practices. Practically, it provides strategic insights for tourism managers to optimize digital platforms, enhance customer engagement, and strengthen competitiveness in an increasingly digital marketplace.